2017
DOI: 10.3390/foods6080064
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Baker’s Yeast Production on Date Extract Using Response Surface Methodology (RSM)

Abstract: This work aims to study the production of the biomass of S. cerevisiae on an optimized medium using date extract as the only carbon source in order to obtain a good yield of the biomass. The biomass production was carried out according to the central composite experimental design (CCD) as a response surface methodology using Minitab 16 software. Indeed, under optimal biomass production conditions, temperature (32.9 °C), pH (5.35) and the total reducing sugar extracted from dates (70.93 g/L), S. cerevisiae prod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 33 publications
1
13
0
Order By: Relevance
“…Optimization of baker's yeast production using date juice as the sole carbon source using the response surface methodology method has been studied by Ali et al [32] and the study showed the success of using date juice in obtaining a good yield of the yeast biomass at the initial conditions of the fermentation process (sugar concentration 70.93 g/L, temperature 32.9°С and pH 5.35).…”
Section: Factor Selection and Organization Of Experimentsmentioning
confidence: 99%
“…Optimization of baker's yeast production using date juice as the sole carbon source using the response surface methodology method has been studied by Ali et al [32] and the study showed the success of using date juice in obtaining a good yield of the yeast biomass at the initial conditions of the fermentation process (sugar concentration 70.93 g/L, temperature 32.9°С and pH 5.35).…”
Section: Factor Selection and Organization Of Experimentsmentioning
confidence: 99%
“…Some selected local strains are sometimes more efficient in biomass production than commercial strains [79,[109][110][111][112][113]. While, from the case of date palm, obtained yeast biomass is different due to the date varieties and the volume of the equipments [114][115][116]. The second advantage is to valorize the renewable low cost substrates and finding other interesting species like Cr.…”
Section: Yeast Biomass Productionmentioning
confidence: 99%
“…Kara Ali [189] studied the production of the biomass of S. cerevisiae on an optimized medium using date extract as the only carbon source in order to obtain a good yield of the biomass. The biomass production was carried out according to the central composite experimental design (CCD) as a response surface methodology.…”
Section: Sourdoughmentioning
confidence: 99%